Formulation of functional beverages from the combination of lime, tomato, and carrot using foam-mat drying method - Kartini Kartini; Alfian Hendra Krisnawan; Lisa Calista Silvanus; Tiffanny Putri Wijaya (Universitas Ahmad Dahlan, 2019)
Â Lime, tomato, and carrot are natural ingredients widely used both as food and herbal medicines particularly because these plants contain various antioxidant compounds such as vitamin C, phenolics, flavonoids, and carotenoids. Since these materials are easily damaged when exposed to high temperatures, any processing methods that involve slight quality changes in the final product are favorable. This study aimed to formulate lime, tomato, and carrot into functional beverages using foam-mat drying method. Lime juice combined with either tomato paste or carrot juice was mixed with egg white and methylcellulose as foaming agents, then whipped using a mixer for 10 minutes to form a stable foam. The foam was placed in a stainless tray, flattened, and dried in an oven at 60Â°C for 5 hours. Once dried, the mass was scraped using a spatula, and the resultant dry powder was then evaluated for its physical characteristics and antioxidant activities using nitrite oxide (NO) method. The produced dry mass of lime, lime-tomato (1:1), and lime-carrot (1:1) had organoleptic characteristics, water content, sugar content, and food additives content in accordance with the Indonesian National Standard (SNI). Also, with the IC50 values of 4248, 4931, and 4218 Âµg/ml, the lime juice and its combination with tomatoes (1:1) and carrots (1:1) can be formulated into functional powder drinks that comply with the SNI quality requirements. Lime-carrot is a better combination than lime-tomato.